Everyday life and locative play: an exploration of Foursquare and playful engagements with space and place. (November 2016) - Saker, Michael; Evans, Leighton
Foursquare is a location-based social network (LBSN) that combines gaming elements with features conventionally associated with social networking sites (SNSs). Following two qualitative studies, this article sets out to explore what impact this overlaying of physical environments with play has on everyday life and experiences of space and place. Drawing on early understandings of play, alongside the flâneur and 'phoneur' as respective methods for conceptualizing play in the context of mobility and urbanity, this article examines whether the suggested division between play and ordinary life is challenged by Foursquare, and if so, how this reframing of play is experienced. Second, this article investigates what effect this LBSN has on mobility choices and spatial relationships. Finally, the novel concept of the 'phoneur' is posited as a way of understanding how pervasive play through LBSNs acts as a mediating influence on the experience of space and place.